Intracranial Bilateral Subdural Hematoma as a Complication of Lumbar Nucleoplasty. Issue 3 (August 2015) - Ceylan, Davut; Köktekir, Ender; Tatarli, Necati; Yaldiz, Can; Yücel, Murat
<x xml:space="preserve">Abstract</x> Nucleoplasty is a percutaneous intradiscal procedure that uses radiofrequencies to reduce intradiscal pressure and the symptoms associated with the contained lumbar disk herniation. Although patients' outcomes and complications with this technique have not been well documented, there are several reported basic complications such as numbness and tingling, but there are also some vital complications such as discitis, bleeding, even anaphylaxis and death. Here we report a case of bilateral intracranial subdural hematoma as a complication of nucleoplasty for the first time in the literature. This complication should be included in the list of potential complications of nucleoplasty and taken into account in the case of patients who present with headache after nucleoplasty.